1997
DOI: 10.1093/humrep/12.10.2313
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 and -2 in human placenta and placental bed after normal and pre-eclamptic pregnancies

Abstract: In pre-eclampsia, the ratio of prostacyclin:thromboxane production rate is decreased favouring the vasoconstrictive thromboxane. One of the rate-limiting steps in prostaglandin synthesis is cyclooxygenase (COX) activity. Therefore, we investigated the expression of COX-1 and COX-2 in human placenta and placental bed. Tissue specimens from the 29th to 40th week of pregnancy were obtained from Caesarean sections after uncomplicated and pre-eclamptic pregnancies before the onset of labour. COX-1 and COX-2 were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…In pregnancies complicated by both IUGR and PE (IUGR-PE), AA was not significantly higher than in controls despite significantly lower percentage LA. Although this might be simply related to the failure to reach statistical power, another possible speculation is related to the increased arachidonic employment in the synthesis of molecules liable to the pathogenesis of PE, such as thromboxane (32). PE and IUGR are two pathological conditions involving an inflammatory process probably beginning in the placenta during the first stages of pregnancy (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pregnancies complicated by both IUGR and PE (IUGR-PE), AA was not significantly higher than in controls despite significantly lower percentage LA. Although this might be simply related to the failure to reach statistical power, another possible speculation is related to the increased arachidonic employment in the synthesis of molecules liable to the pathogenesis of PE, such as thromboxane (32). PE and IUGR are two pathological conditions involving an inflammatory process probably beginning in the placenta during the first stages of pregnancy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Increases of NEFA and triglycerides in the fetal circulation of only IUGR-PE could be the reflection of changes in placental lipase activities (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in this pathological condition characterized by placental insufficiency but also by a vascular damage in which the atherogenic role of lipids and lipoperoxidation have been well established (18).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that Cox-2 is highly expressed in endometriosis (Ota et al 2001, Chishima et al 2002. Other studies show that Cox-2 is strongly expressed in endometrial adenocarcinomas (Uotila et al 2002), but not in preeclampsia (Wetzka et al 1997). …”
Section: Cyclooxygenase-2 (Cox-2)mentioning
confidence: 91%
“…Wetzka et al reported that there were no significant differences in COX-1 and COX-2 expression between precritical and postcritical PIH sufferers. 8) On the other hand, Borekci et al reported that the COX-1 and COX-2 activity in severe and mild PIH patients was significantly lower than that in a normal pregnant group. 9) No differences in PGI 2 synthase or TXA 2 synthase were reported between normal and PIH pregnant groups.…”
Section: Discussionmentioning
confidence: 97%